Historical development of the ward nurse position in the Czech Republic - Marková, Eva; Bártlová, Sylva (Journal of Nursing, Social Studies and Public Health, 2013)
Ward nurse represents the basic level of managers in a healthcare organisation. The ward nurse position has changed in the past in relation to the development of the nursing sector, nursing care itself and the management of work teams and human resources. Relevant information on the ward nurse position can be obtained from historical sources. This overview article summarises information about ward nurse’s work activities from studies carried out from the 1970s up to the present. We found that the ward nurse position was established due to the need to organise the operation in wards and coordinate activities of e.g. health professionals in patient care. In some periods there has been a tendency to merging the ward nurse and head nurse positions. In the past as well as today, a healthcare facility defines the ward nurse’s job description. Cooperation and teamwork play an important role in their work, but it is also a source of potential conflicts. The research showed that the activities of ward nurse are quite extensive and often include activities that are not necessarily related to their responsibilities. Their activities have been extended from a person originally responsible for economic and administrative run of the care unit towards a manager responsible for organising the work, management of work teams and human resources.
Keywords: History of Nursing; lidé; Nurse Clinicians; dějiny ošetřovatelství; Nursing Care; ošetřovatelská péče; řízení ošetřovatelské péče; popis práce; zdravotní sestry v klinické praxi; Job Description; Humans